Use of propionic acid additions to enhance zinc removal from mine drainage in short residence time, flow-through sulfate-reducing bioreactors. (1st February 2023) - Gandy, Catherine J.; Gray, Neil D.; Mejeha, Obioma K.; Sherry, Angela; Jarvis, Adam P.
Abstract: The effectiveness of liquid carbon additions to enhance zinc removal in laboratory-scale short hydraulic residence time (19 h) compost bioreactors receiving synthetic mine water with a high influent zinc concentration (45 mg/L) was investigated. Effective removal of such elevated zinc concentrations could not be sustained by sulfate reduction and/or other attenuation processes without carbon supplementation. Propionic acid addition resulted in improved and sustained performance by promoting the activities of sulfate reducing bacteria, leading to efficient zinc removal (mean 99%) via bacterial sulfate reduction. In contrast, cessation of propionic acid addition led to carbon limitation and the growth of sulfur oxidising bacteria, compromising zinc removal by bacterial sulfate reduction. These research findings demonstrate the potential for modest liquid carbon additions to compost-based passive treatment systems to engineer microbial responses which enhance rates of zinc attenuation in a short hydraulic residence time, enabling remediation of highly polluting mine drainage at sites with limited land availability. Graphical abstract: Image 1 Highlights: Carbon limitation is the key constraint to effective Zn removal. Propionic acid addition promotes the activities of sulfate reducing bacteria. Cessation of carbon addition leads to substrate oxidation which limits Zn removal. Enhanced passive treatment can remove >95% zinc in a short hydraulic residence time.